Features of democratic reforms in Jordan - A. V. Krilov (Vestnik MGIMO-Universiteta, 2013)
The article presents the analysis of the political, demographic and other aspects of the Palestinian community in Jordan, which has become a major factor in the Jordanian political life since the beginning of Arab-Israeli conflict and Israel’s occupation of the West Bank. The results of the research show that political and social-economic reforms of Jordanian King Abdullah II haven’t improve the status of the Palestinians, especially the status of the Palestinian refugee camps residents in Jordan. In contrast to the indigenous population (Bedouin population and some Caucuses or Circassian communities) they have no political representation, no access to power, no competitive education and business activity is under restrictions. Today the Palestinians and their descendants make up in Jordan at least two thirds of the population and most of them support the Hamas and other radical Islamic groups. Since the aftermath of the Black September Civil War (1970-1971) they continue to be the main factor that can destabilize the internal situation in the Hashemite Kingdom. Current unfavorable economic conditions and the extremely volatile situation on the borders of Jordan with Syria, Iraq and the area of the Palestinian-Israeli conflict are most likely to the growth of Islamist activity, including Islamic extremists calling for the overthrow of the Hashemite monarchy. In this context the possibility of mass anti-monarchy protests can’t be excluded. At the same time King Abdullah and his political proponents are well aware of this challenge and the dependence on the development of the situation in the Middle East, as well as financial and military support of powerful Western States and the Golf oil-producing monarchies. In seeking to preserve the existing status quo Jordanian authorities would deliberately put the country in a state of dependency on the political interests of the U.S. and Saudi Arabia, in return for all kinds of preferences, including military aid if a threat to the security of the Kingdom is expected.